(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Stinging catfish, Shing (Heteropneustes fossilis) is been cultured in Bangladesh which is one of the most popular and highly valuable fish species. A total of 120 diseased H. fossilis were collected from twenty five fish farms in greater Mymensingh region, Bangladesh between November 2013 to February 2014. Remarkable clinical symptoms of the affected fishes were loss of equilibrium and, erosions at the bases of fins and tail, hemorrhages and skin lesions on body surface, profuse mucous secretion and congestion along with enlargement of most of the internal organs. Three different kinds of selective media were used for the isolation of total population of bacteria from the affected fishes. A number of biochemical tests were performed for the identification of the isolated bacteria. Commercially available panel of antibiotics were used for the determination of sensitivity of the isolated bacteria. A total of 85 bacterial strains were isolated and the isolated were Aeromonas hydrophila, A. salmonicida, A. sobria, Pseudomonas angulliseptica, P. fluorescens and Vibrio anguillarum. Aeromonas spp. appeared to be the main pathogen in the diseased fishes. Among the isolated spp of bacteria distribution of Aeromonas species was as follows: A. hydrophila 34 (40.00%), A. salmonicida 14 (16.47%), A. sobria 8 (9.41%) as well as 5 (5.88%) unidentified Aeromons strains. The other isolated of Pseudomonas anguliseptica, P. fluorescens, Vibrio anguillarum and Vibrio spp were distributed as 12 (14.11%), 4 (4.70%), 3 (3.52%) and 5 (5.88%), respectively in infected H. fossilis. However, results of antibiotic sensitivity test revealed that all the bacterial isolates of H. fossilis were found more or less resistant to all most all the antibiotics with the exception of ciprofloxacin and levofloxacinn which were found highly sensitivity against all the strains of Aeromonass pp. and other species of bacteria. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 116-124